AFRICAN MISTLETOES (LORANTHACEAE); ETHNOPHARMACOLOGY, CHEMISTRY AND MEDICINAL VALUES: AN UPDATE - Adesina, Simeon K.; Illoh, H. C.; Johnny, Imoh I.; Jacobs, Imoh E. (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Mistletoes of the Loranthaceae and Viscaceae are hemiparasitic plants and their preparations in the form of injectable extracts, infusions, tinctures, fluid extracts or tea bags are widely used in various cultures in almost every continent to treat or manage various health problems including hypertension, diabetes mellitus, inflammatory conditions, irregular menstruations, menopause, epilepsy, arthritis, cancer, etc. The medicinal values of some species of Mistletoes (Loranthaceae) growing in the West African sub-region have been reviewed along with some considerations of their chemistries and local uses. These have been compared with Mistletoes (Loranthaceae and Viscaceae) growing elsewhere in Europe and Asia. This review has attempted to update our knowledge on the values of these hemi-parasites which belong to the genera – Globimetula, Phragmanthera, Agelanthus and Tapinanthus, and which have, for years, been seen as only devastating and notorious plants. They are also seen as epiphyting economic, ornamental and medicinal plants. The hemi-parasitic plants (Mistletoes) are not well understood as very little is known about their biology (taxonomy, host/plant relationship, ecology, toxicology, physiological characteristics, etc.) and chemistry (chemical constituents’ profile). Some pharmacological studies carried out on the various crude alcoholic extracts and purified fractions have, however, revealed that mistletoes showed hypotensive, hypoglycaemic, antilipidaemic, anti-oxidative, anti-inflammatory, antimicrobial, etc. effects and were non-toxic in experimental animals at the doses used. The findings showed that mistletoes can be very useful as medicinal agents in ameliorating health problems such as diabetes mellitus, hypertension, arthritis, pain, cancer and a host of other ailments if properly studied and developed.